1995
DOI: 10.1021/tx00046a007
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the p-Alkyl Substituent on the Isomerization of o-Quinones to p-Quinone Methides: Potential Bioactivation Mechanism for Catechols

Abstract: Previously, we have shown that an additional bioactivation pathway for the hepatocarcinogen safrole (1-allyl-3,4-(methylenedioxy)benzene) exists which may contribute to its toxic effects: initial O-dealkylation of the methylenedioxy ring, forming the catechol, hydroxychavicol (HC, 1-allyl-3,4-dihydroxybenzene), 2-electron oxidation to the o-quinone (4-allyl-3,5-cyclohexadien-1,2-dione), and isomerization, forming the more electrophilic p-quinone methide (2-hydroxy-4-allylidene-2,5-cyclohexadien-1-one) [Bolton,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 22 publications
4
76
0
Order By: Relevance
“…The study of the m/z shift as well as the fragmentation pathways observed for the quasi-molecular ions have shown that addition of the base could occur on both the C6 and C9 sites of the steroid B ring in its quinone-methide form. Although compounds attributed to the degradation of an adduct formed by nucleophilic attack of the base on C9 position have already been identified [39,42,43], the corresponding adducts had never been clearly evidenced by LC-MS n until this work. Some complementary work needs now to be developed in order (1) to achieve a complete chromatographic separation of the C6 and C9 adducts which coelute in our LC-MS experiments and (2) to improve the understanding of the particular fragmentation process of this adduct.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The study of the m/z shift as well as the fragmentation pathways observed for the quasi-molecular ions have shown that addition of the base could occur on both the C6 and C9 sites of the steroid B ring in its quinone-methide form. Although compounds attributed to the degradation of an adduct formed by nucleophilic attack of the base on C9 position have already been identified [39,42,43], the corresponding adducts had never been clearly evidenced by LC-MS n until this work. Some complementary work needs now to be developed in order (1) to achieve a complete chromatographic separation of the C6 and C9 adducts which coelute in our LC-MS experiments and (2) to improve the understanding of the particular fragmentation process of this adduct.…”
Section: Resultsmentioning
confidence: 94%
“…Alternatively, the nucleophilic attack at the C9 position was also proposed for the formation of some estrogen quinone-glutathione adducts, but the occurrence of such species could not be evidenced [39,42]. In this case, the unstable character of such adducts was also reported and only products formed by elimination of glutathione (i.e., 9-dehydro-4OHE and 9-dehydro-2OHE from 4OHE-o-quinone and 2OHE-o-quinone, respectively) were identified as the end products of the degradation of such transient adduct species [39,42]. …”
Section: Ms N Experiments On the M/z 557 Ions From 3: Evidence For A mentioning
confidence: 99%
“…These findings are not unexpected as the literature suggests ortho-quinones do not usually undergo adduct formation with cellular macromolecules, instead their damage is usually mediated through an increase in oxidative stress (Chichirau et al, 2005;O'Brien 1991;Monks et al, 1992). Although ortho-quinones may isomerize to para-quinone methides in vivo, a quinone derivative known to form covalent adducts with cellular macromolecules (Powis 1987), this process is unlikely to occur as NDGA is substituted at the benzylic carbon, which severely hinders the isomerization process (Iverson et al, 1995).…”
Section: Cytochrome P450-mediated Formation Of Reactive Metabolitesmentioning
confidence: 65%
“…Structural features of the lignans suggest their potential for oxidation to quinone derivatives, a class of compounds known to be electrophilic reactive intermediates (Bolton et al, 1994;Iverson et al, 1995). Since SDG is unlikely absorbed due to the polar nature of the glycosidic groups, it was not investigated for their potential to undergo hepatic P450-mediated bioactivation to a reactive intermediate.…”
Section: Cytochrome P450-mediated Formation Of Reactive Metabolitesmentioning
confidence: 99%
“…These results are entirely in accord with earlier studies by Bolton and co-workers who trapped para-quinomethanes as their glutathione adducts and showed that the ortho-quinone rearrangement is base catalyzed. 22,23 The different .…”
mentioning
confidence: 99%